Elastin turnover in malignant solid tumors. (22nd August 2013) - Starcher, Barry; Sauter, Edward; Ho, Coty
Abstract: Desmosine, a crosslinking amino acid unique to elastin, was investigated as a possible biomarker for cancer. Twenty-eight normal controls, median age 67 years, had a median value for urine desmosine of 43.5 picomoles desmosine/mg creatinine. The median for 19 untreated cancer subjects of similar age was significantly higher (175 picomoles desmosine/mg creatinine, p < 0.001). Urine desmosine levels in 55 subjects currently receiving chemotherapy, as well as 67 individuals who had survived cancer and were currently clinically disease free, were not significantly different from controls. Our findings indicate that elastin is being turned over in malignant solid tumors, releasing significantly elevated levels of desmosine in the urine.